Chemical characteristics of coastal rainwater from Puducherry to Neithavasal, Southeastern coast of India - Chidambaram, S.; Paramaguru, P.; Prasanna, Mohan Viswanathan; Karmegam, U.; Manikandan, S. (Springer, 2014)
The chemistry of the rainwater indirectly reflects the composition of the ions in the atmosphere. The study of the rainwater gains its own importance as it forms the basis for the agricultural, domestic and drinking water. Twelve rainwater samples were collected along the southeastern coast of India during southwest monsoon. The samples were analyzed for the major anions (Cl−, SO4 2−, PO4 3− and HCO3 −) and cations (Na+, K+, Ca2+ and Mg2+). The majority of the samples reflect acidic pH. The general dominance of the cations is in the order of Na+ > Ca2+ > K+ > Mg2+ and that of anions is HCO3 − > Cl− > SO4 2− > PO4 3−. The water is classified as calcium bicarbonate to sodium bicarbonate type. The decrease of pH value also increases the pCO2. In order to study the impact of acidic and alkaline species on rainwater, correlation coefficients were determined for establishing the relationship between different ions. Good correlation was established between cations, and sulfate has no correlation with other ions and pH. Factor analysis reveals that land use pattern, marine source and methanogenesis from the tidal influenced mangroves play a major role in determining the rainwater chemistry of the region.